2019
DOI: 10.1016/j.laa.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Aron–Berner extensions of triple maps with application to the bidual of Jordan Banach triple systems

Abstract: By extending the notion of Arens regularity of bilinear mappings, we say that a bounded trilinear map on Banach spaces is Aron-Berner regular when all its six Aron-Berner extensions to the bidual spaces coincide. We give some results on the Aron-Berner regularity of certain trilinear maps. We then focus on the bidual, E * * , of a Jordan Banach triple system (E, π), and investigate those conditions under which E * * is itself a Jordan Banach triple system under each of the Aron-Berner extensions of the triple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
2
0
3
Order By: Relevance
“…In this article, we will be dealing with the above-mentioned extension in various situations, especially π * * * * for the extension of the triple product π of a JB-triple system. However, in the most general setting, every such map f : X ×Y ×Z → W has six generally different extensions from X * * × Y * * × Z * * to W * * (see Aron and Berner [2]; more explicit properties of these extensions are investigated in the forthcoming work [16]).…”
Section: 2mentioning
confidence: 99%
“…In this article, we will be dealing with the above-mentioned extension in various situations, especially π * * * * for the extension of the triple product π of a JB-triple system. However, in the most general setting, every such map f : X ×Y ×Z → W has six generally different extensions from X * * × Y * * × Z * * to W * * (see Aron and Berner [2]; more explicit properties of these extensions are investigated in the forthcoming work [16]).…”
Section: 2mentioning
confidence: 99%
“…Also the bounded tri-linear map f is said to be Aron-Berner regular when all natural extensions are equal, that is, f i * * * * i = f j * * * * j = f r * * * * r = f * * * * = f t * * * * s = f s * * * * t holds. For example in [6] it has been shown that the tri-linear map f : X × X × X −→ X defined by…”
Section: Introductionmentioning
confidence: 99%
“…Como 𝐴 é Arens-regular, é bem conhecido que todas as extensões de Aron-Berner de 𝐴 coincidem e são separadamente 𝜔 * -𝜔 * -contínuas. Também é conhecido que, como todo operador linear contínuo de 𝐸 em 𝐹 é fracamente compacto, tais extensões são genuínas (para todas estas informações veja [15,51]). Aplicando a Proposição 5.1.7 concluímos que todas as extensões de Aron-Berner de 𝐴 são separadamente quase Dunford-Pettis.…”
Section: Operadores Multilineares Separadamente Quase Dunford-pettisunclassified
“…A construção original de Arens para o caso bilinear, que depois foi generalizada para o caso multilinear por Aron e Berner, é a seguinte: dado um operador bilinear 𝐴 ∶ 𝑋 1 × 𝑋 2 ⟶ 𝑌 entre espaços de Banach, defina os seguintes operadores bilineares: 𝐴 * ∶ 𝑌 * × 𝑋 1 ⟶ 𝑋 * 2 , 𝐴 * (𝑦 * , 𝑥 1 )(𝑥 2 ) = 𝑦 * (𝐴(𝑥 1 , 𝑥 2 )), 𝐴 * * ∶ 𝑋 * * 2 × 𝑌 * ⟶ 𝑋 * 1 , 𝐴 * * (𝑥 * * 2 , 𝑦 * )(𝑥 1 ) = 𝑥 * * 2 (𝐴 * (𝑦 * , 𝑥 1 )) e 𝐴 * * * ∶ 𝑋 * 1 × 𝑋 * * 2 ⟶ 𝑌 * * , 𝐴 * * * (𝑥 * * 1 , 𝑥 * * 2 )(𝑦 * ) = 𝑥 * * 1 (𝐴 * * (𝑥 * * 2 , 𝑦 * )). É imediato que 𝐴 * * * é um operador bilinear que satisfaz a igualdade 𝐽 𝑌 •𝐴 = 𝐴 * * * •(𝐽 𝑋 1 , 𝐽 𝑋 2 ), isto é, 𝐴 * * * é uma extensão bidual de 𝐴. Desde então, 𝐴 * * * tem sido chamada de extensão de Arens de 𝐴 e fortemente estudada na teoria (veja, por exemplo, [15,20,21,22,51,74,75,80]). Seguindo a mesma técnica, define-se a extensão de Arens de um operador 𝑚-linear 𝐴, denotada por 𝐴 * (𝑚+1) , que também vem sendo muito estudada (veja, por exemplo [13,14,17,19,26,29,39,56]).…”
Section: Introductionunclassified
See 1 more Smart Citation